Effects of base ingredient in cooked molasses blocks on intake and digestion of prairie hay by beef steers - Greenwood, R.H.; Titgemeyer, Evan C.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Blocks based on cooked beet molasses, cane molasses, or concentrated separator by-product, CSB) were tested to compare their effects on intake and digestion of prairie hay by beef steers. All blocks contained at least 30% crude protein. Steers fed the cooked molasses blocks consumed and 22% more forage than control steers, but forage intakes were not different among the three different blocks. Intakes of digestible organic matter and neutral detergent fiber, indicators of energy available to the steers, were increased 38 and 29% respectively, by block supple-mentation but were not different among the three blocks. However, total tract organic matter and neutral detergent fiber digestibilities, expressed as a percent of intake, were slightly higher for steers fed the beet molasses block than those fed the cane molasses block or the CSB block. In summary, supplementation with cooked molasses blocks that contained adequate degradable protein increased forage intake and digestion. Generally, blocks made from the different by-products elicited similar responses, though steers fed the beet molasses product tended to have greater digestibilities than those fed blocks made from cane molasses or concentrated separator by-product.
Keywords: Beef; Steers; Forage; Intake; Digestability; Cooked molasses blocks